Correlation between ESP syllabus design and material adaptation based on needs analysis: A review of literature - Jamaluddin Jamaluddin; Muhammad Hanafi; Andi Sadapotto (UAD TEFL International Conference)
This paper aims to review the development of ESP Syllabus design theory and material adaptation based on the need’s analysis of the students. Besides, it explores and presents the references on the relationship between ESP syllabus design and material adaptation. ESP syllabus design deals with the kinds and importance of a syllabus. The materials in it discuss authenticity, material evaluation, and material writing. Need analysis covers the meaning, type, practice, and register of an analysis.